Managing and Financing Water for Growth in Thailand Highlights of a National Dialogue on Water (OECD Studies on Water, 2022)
The National Dialogue on Water in Thailand was initiated in 2021 under the regional initiative with the Ministry of Environment of the Republic of Korea (MoE), the Asia Water Council (AWC) and the OECD. The Dialogue covers two main topics selected by the Government of Thailand (ONWR). The first one is water demand management, with a focus on the Eastern Economic Corridor. The second one is financing water supply and sanitation. Both combine to support a sustainable and resilient development pathway for Thailand's fast-growing economy. The analyses and policy recommendations cover issues such as the design of economic policy instruments, water allocation regimes, increasing demand for reclaimed water, or benchmarking the performance of water utilities, and blended finance for water supply and sanitation services. They are informed by the expertise of Thai stakeholders, the OECD and the Asia Water Council. They can be a source of inspiration in other contexts in South East Asia and globally